Peptides to combat viral infectious diseases (2020)
Viral infectious diseases have resulted in millions of deaths throughout history and have created a significant public healthcare burden. Tremendous efforts have been placed by the scientific communities, health officials and government organizations to detect, treat, and prevent viral infection. However, the complicated life cycle and rapid genetic mutations of viruses demand continuous development of novel medicines with high efficacy and safety profiles. Peptides provide a promising outlook as a tool to combat the spread and re-emergence of viral infection. This article provides an overview of five viral infectious diseases with high global prevalence: influenza, chronic hepatitis B, acquired immunodeficiency syndrome, severe acute respiratory syndrome, and coronavirus disease 2019. The current and potential peptide-based therapies, vaccines, and diagnostics for each disease are discussed.